Società plurale: quali rapporti scuola-famiglia? - Santelli Beccegato, Luisa (Rivista Italiana di Educazione Familiare, 2015)
The analisys considers the Italian situation related the foreing pupils presence and extends reflections and projects to a general vision of school’s activities interpretated as a ‘friendly’ school. These expression want to understand a school of all and for all. And this involves to realize a school serious and meanwhile able to welcome, marked with high levels of communications where the dialogue among all subjects, inside and outside school, is promoted and supported. It requires, particularly, to pass from parents as ‘user’ to parents as ‘partner’: a very difficult itinerary ever more complex with migrant families where the problems in general thicken for a weak Italian language’s knowledge and poor economic’s and time’s availability. At the right moment, it is opportune to mention some good pratices realised in our Country where the school-family connection is often widened to associations and local autorities and the school becomes point of reference in a system of alliance.